Influência da otimização de trajetórias ociosas do bico extrusor em processo de manufatura aditiva - Zanotto, Thiago Tavares (2017)
Additive manufacturing is characterized by adding material layer by layer, thus presenting little geometric limitation. This technology has revolutionized the production process and can even be employed as part of the final product. One of the existing technologies is based on the material extrusion principle, which is characterized by adding a polymeric filament through an extruder head. One of the stage of the process planning in this principle is the path planning, where the strategy and the sequence of the material deposition is defined. In this process there are idle movements (without material deposition) of the extrusion head. Several studies have already been carried out to minimize the idle time, involving path optimization algorithms, but without considering the possible side effects caused by this optimization in the manufactured parts. Therefore, the aim of this work is to evaluate the influence of path planning with and without optimization on mechanical properties, dimensional and building time of manufactured parts based in the principle of material extrusion, using polylactic acid (PLA). An experiment also was performed where it was possible to analyze the influence of the idle time of the extruder head during the material deposition in the same layer. For that an interruption of the extruder head during the material deposition was programmed. Different numbers of specimens were fabricated using 3D Cloner printer. Building time and dimensional evaluation were performed, together with tensile and 3-point bending tests. The results of tensile and bending showed a variation of 7% and 10%, on tensile at break, respectively when compared to the different path planning tested. In the experiments with interruption of the nozzle extruder the variation reached up to 46% (decrease in flexural strength). Regarding the building time between the different path planning tested, there was a difference up to 42.7% and in the dimensional evaluation it was observed small variation between the tested methods.